Pengaruh Influencer Marketing dan Online Customer Reviews terhadap Brand Awareness Produk Coklat Dubai Don Bakeshop - Fatma Listari; Muhammad Thoyib Amali (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the effect of Influencer Marketing and Online Customer Reviews on Brand Awareness of Coklat Dubai Don Bakeshop. The research refers to the Influencer Marketing theory, Online Customer Review and Brand Awareness theory. A quantitative method was applied through a survey of 384 respondents aged 17–35, selected using purposive sampling. The respondents were active social media users who had heard of or purchased the Coklat Dubai Don Bakeshop product. Data were collected via structured questionnaires and analyzed using multiple linear regression with SPSS. The results show that both Influencer Marketing and Online Customer Reviews have a positive and significant impact on Brand Awareness, with Influencer Marketing having a stronger effect. These findings confirm the effectiveness of digital strategies in building brand recognition in the local culinary market.